1994
DOI: 10.2307/5548
|View full text |Cite
|
Sign up to set email alerts
|

Egg Load and the Decision to Host-Feed in the Parasitoid, Aphytis melinus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. We make and test predictions about how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 37 publications
6
75
1
1
Order By: Relevance
“…These models predict existence of a threshold egg load below which host-feeding occurs. While these predictions qualitatively agree with experimental results of Collier et al (1994) who showed that probability of host-feeding declines with the egg load, a similar experiment by Rosenheim and Rosen (1992) does not show such a relationship.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…These models predict existence of a threshold egg load below which host-feeding occurs. While these predictions qualitatively agree with experimental results of Collier et al (1994) who showed that probability of host-feeding declines with the egg load, a similar experiment by Rosenheim and Rosen (1992) does not show such a relationship.…”
supporting
confidence: 78%
“…On the level of individuals this trade-off leads to dynamical programming which predicts the best feeding behavior of a parasitoid. The general prediction of these models is that there is a threshold in the egg load; if the egg load is below the threshold, host-feeding appears (Collier et al 1994). However, these models do not consider population dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both types of parasitoids, the decisions of the females regarding when to search for food and when to search for oviposition sites are triggered by physiological parameters. Indeed, in all the mathematical models of parasitoid behaviour developed so far, foraging decisions have been shown to be strongly dependent on the pattern of allocation of nutrients from adult food to egg production and survival (Houston et al 1992;Chan & Godfray 1993;Collier et al 1994;Heimpel et al 1994;Collier 1995a;Sirot & Bernstein 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most comprehensive theoretical models of resource allocation to reproduction and survival have been developed in order to predict female reproductive behaviour in a group of insects known as parasitoid wasps (Houston et al 1992;Chan & Godfray 1993;Collier et al 1994;Godfray 1994;Heimpel et al 1994Heimpel et al , 1998Collier 1995a). These models have provided us with an unprecedented understanding of the behavioural tradeo¡s and physiological constraints faced by foraging insects.…”
Section: Introductionmentioning
confidence: 99%